2006
DOI: 10.1038/sj.onc.1209496
|View full text |Cite
|
Sign up to set email alerts
|

Members of the hSWI/SNF chromatin remodeling complex associate with and are phosphorylated by protein kinase B/Akt

Abstract: In an adenosine triphosphate (ATP)-dependent process, the hSWI/SNF chromatin remodeling complex functions to alter chromatin structure, thereby regulating transcription factor access to DNA. In addition to interactions with transcription factors and recognition of acetylated histone residues, the chromatin remodeling activity of hSWI/SNF has also been shown to respond to a variety of cell signaling pathways. Our results demonstrate a novel interaction between the serine/threonine kinase Akt and members of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 43 publications
0
24
0
1
Order By: Relevance
“…We and other groups have shown that INI1/hSNF5 regulates multiple pathways and genes including cyclinD1/cdk/p16 pathway, mitotic checkpoint, interferon signaling and hedgehog signaling in RTs cells (11,12,14,15,41). Here, we have shown, for the first time, that INI1/hSNF5 represses Aurora A selectively in RT cells.…”
Section: Discussionmentioning
confidence: 47%
“…We and other groups have shown that INI1/hSNF5 regulates multiple pathways and genes including cyclinD1/cdk/p16 pathway, mitotic checkpoint, interferon signaling and hedgehog signaling in RTs cells (11,12,14,15,41). Here, we have shown, for the first time, that INI1/hSNF5 represses Aurora A selectively in RT cells.…”
Section: Discussionmentioning
confidence: 47%
“…BAF155 has been shown to stabilize BAF47, BRG1 and BAF60A by attenuating their proteosomal degradation (Sohn et al, 2007). BAF155 may be phosphorylated by Akt, suggesting that PI3K/Akt signaling may modulate SWI/SNF function (Foster et al, 2006). Loss of BAF155 has been reported in a small number of cancer cell lines .…”
Section: Swi/snf Subunits and Their Role In Gene Regulation And Cancermentioning
confidence: 99%
“…Colony stimulating factor (CSF-1) is another main driving cytokine for macrophage recruitment [102], which is transcriptional controlled by the SWI/SNF complex [108]. Although members of the SWI/SNF chromatin-remodeling complex have been shown to interact with and be phosphorylated by PKB [109], a direct contribution of PKB in the context of SWI/SNF mediated CSF-1 expression is still missing. Nonetheless, PKB has been shown to be required for macrophage chemotaxis in response to both CSF-1 and CCL2 [110].…”
Section: Pkb Regulated Macrophage Functionmentioning
confidence: 99%